Factors Influencing ERP system usage in manufacturing and service industries: a comparative study using PLS-SEM and fsQCA - Radić, Aleksandra; Arsić, Sanela; Nikolić, Đorđe; Bobek, Samo; Sternad Zabukovšek, Simona (Serbian Journal of Management, 2026)
Enterprise Resource Planning (ERP) systems represent an important technological infrastructure for enhancing operational efficiency and strategic decision making in various industries. This study examines the key determinants influencing the adoption of ERP systems, with a particular focus on organizations operating in the manufacturing and service sectors in the Western Balkans region. In order to empirically evaluate the proposed conceptual framework, Partial Least Squares Structural Equation Modeling (PLS-SEM) and Fuzzy Set Qualitative Comparative Analysis (fsQCA) were employed. In this way, both linear relationships and configuration pathways underlying ERP implementation behavior were captured. The results of the PLS-SEM analysis show that constructs such as work compatibility, perceived usefulness and external factors are statistically significant predictors of users’ attitudes towards using ERP systems. In addition, a significant relationship was found between attitude and actual use of ERP systems, with user experience serving as a moderating variable. Notably, the multi-group analysis revealed no significant differences in intentions, attitudes or preferences between users from the manufacturing and service sectors. The results of the fsQCA study also show that work compatibility and perceived usefulness are the core present conditions necessary for effective ERP adoption. This study contributes to the existing literature by integrating multiple analytical approaches to explore the complexity of ERP usage. Additionally, it provides practical insights for enterprise managers, ERP vendors and policymakers.
Keywords: ERP system; manufacturing sector; service sector; PLS-SEM; fsQCA